Selected writings from the Journal of the Saskatchewan Mathematics Teachers' Society : celebrating 50 years (1961-2011) of Vinculum - Chernoff, Egan J.; Russell, Gale; Sriraman, Bharath (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
Selected writings from the Journal known, over time, as: Saskatchewan Mathematics Teachers' Society Journal; Saskatchewan Mathematics Teachers' Society news/journal; Numerator (Saskatoon); and, Vinculum (Saskatoon).
Keywords: Mathematics -- Study and teaching -- Saskatchewan.; Mathematics -- Study and teaching -- Canada.; Education -- Teaching -- Subjects -- Mathematics.; Teaching of a specific subject.; Teaching of reading, writing and numeracy.; Educational: Mathematics and numeracy.; elektronické knihy; electronic books